BETWEEN HISTORY AND LEGEND: FOOD, CULTURE AND POLITICS AT THE ESTE COURT OF FERRARA - A PSEUDOSCIENTIFIC APPROACH TO REIGNING. - Andrea Guiati (European Scientific Journal, ESJ, 2014)
Gastronomy, by which I mean the pleasure and the luxury ofthe dinner table, was always a passion of the ambitious Este family. They were rulers of Ferrara from the beginning of the 13th to the end of the 16th centuries. The Estensi, as they were called, fancied fine clothes, elaborate ceremonies, beautiful art works and succulent food. Today's Ferraresi have adopted many of their customs and habits. If they can afford it, that is. The Este laid a splendid table. Famous chefs, such as Cristoforo Messibugo, whose name is still revered in culinary circles, spent their time inventing dishes for the many courses that typically made up one of these gargantuan feasts. And what a sparkling life was lived in those splendid times! When I grew up in Ferrara in the 1960s and early 1970s very few people seemed to remember the city‘s glorious past, the castle moat had become one of the favorite dumping grounds to rebellious teenagers who would throw in it outdoor bar furniture, bicycles and whatever else they found lying around late at night. The breathtaking castle was in need of repairs. Via delle Volte with its arches and cobblestones had become home to prostitutes and small-time thieves, the wall surrounding the city was crumbling down. The Estensi‘s work had been lost, not only through fire and earthquake, but also due to civic disregard.